Geological and Geochemical Characteristics of Hydrocarbon Seeps in the Continental Margin of Southwestern Crimea, Laspi Bay - E. A. Krasnova; A. A. Budnikov; I. N. Ivanova; A. I. Khurchak; A. S. Gryaznova; О. V. Krylov; T. V. Malakhova (Georesursy, 2024)
In 2023, comprehensive studies of shallow-water methane gas emissions were conducted during expeditionary work in the coastal area of Laspi Bay (southwestern coast of Crimea). The research included determining the component and isotopic composition of bubble gas, measuring methane concentration in the gas emission area, estimating bubble flux rates, and measuring hydrophysical parameters above the seep site. The obtained results of the carbon isotopic composition of methane and ethane in the studied samples corresponded to (δ13Cmean = –36.0 ± 0.8‰, δ13Cmean = –37.5 ± 0.2‰, respectively) and indicate the presence of thermocatalytic methane migration along fault systems. It was found that the methane seeps of the Crimean coast are relatively low-flow, with a specific flux ranging from 5 to 10 m3 year-1 from an individual seep. The presented temporal dynamics of dissolved СН4 concentration above the seep and changes in the isotopic ratio of δ13C-СН4 in bubble gas indicate the constancy of the process over time and the absence of connection with external hydrological changes in the water area. The obtained ratios of the carbon isotopic composition of methane and ethane demonstrate that the gas mixture was most likely generated from source organic matter of marine origin, and one of the main sources of hydrocarbon fluids is the Upper Eocene and Oligocene deposits in the Western Black Sea basin.